Analisis Kritis Pencatuman Klausula Baku pada Perjanjian Kredit Kendaraan Bermotor di Kota Bima - Syamyati Syamyati; Adnan Adnan; Musmuliadin Musmuliadin (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study critically examines the inclusion of standard clauses in motor vehicle credit agreements in Bima City and their conformity with the principles of balance, good faith, and consumer protection. This study employs an empirical legal research method with sociological and statutory approaches. Data were collected through interviews, observations, and document studies involving 10 consumers and two financing companies. The findings show that all of the agreements examined contained exoneration clauses, unilateral authorization clauses, and unilateral choice-of-law clauses. In addition, most of the documents also included clauses on unilateral interest rate changes and automatic renewal. The signing process was brief, lasting approximately 15 to 30 minutes, without adequate room for negotiation. The agreement documents also used small font sizes, ranging from 8 to 10 points, and were not accompanied by sufficient explanations from the leasing companies. These practices conflict with Article 18 of the Consumer Protection Law, the principle of balance, and the principle of good faith because they place consumers in a weaker position and create an imbalance of rights and obligations between the parties. These clauses may also be declared null and void by law. Therefore, this study recommends strengthening supervision by the Financial Services Authority and local governments, improving consumers’ legal literacy, and ensuring strict law enforcement against business actors who violate consumer protection provisions.